THE EFFECT OF FLY SWATTER GAME ON STUDENTS VOCABULARY MASTERY FOR ELEVENTH GRADE - Kamila, Athalla Shafa; Faliyanti, Eva; Latif, Amirudin; Kusumawati, Fitri Palupi (Premise: Journal of English Education and Applied Linguistics, 2024)
In learning English, vocabulary is one of the language aspects and is the most important component as a communication tool that students must master as a basis for mastering English. Vocabulary means basic knowledge and useful material in the form of words that are always used by students in learning a particular language. The aim of this research is to examine the effect of using the fly swatter game on the learning and vocabulary mastery of class XI students at SMA Negeri 2 Metro. This study used a quantitative method with a quasi-experimental design. The researcher used the fly swatter game as a teaching technique in the experimental class, while the conventional teaching technique will used in the controlled class. The results of the study using hypothesis testing show that the first test uses a significance level of 5% or a significance level of 0.05. sig. (2-tailed). The t-count (1.420) is lower than the t-table (2,000) with a significance of (0.165) > 0.05. Therefore, it can be said that teaching English vocabulary mastery using the Fly Swatter Game is effective but not significant.